Effect of Packing System, Calcium Chloride and Chlorine on the Storage Life of Strawberry Fruits (Fragaria ananassa cv. Kordistan) - Fatemeh Mozhdehi; Vahid Abdossi; Sepideh Kalatejari (Journal of Basic & Applied Sciences, 2021)
Effect of packing system, calcium chlorite and chlorine was evaluated on storage life of strawberry fruits. Fruits were treated with commercial grade of chlorine (calcium hypochlorite at 0, 25, 50 and 100 ppm and sodium hypochlorite at 0, 25, 50 and 100 ppm with distilled water) for one minute and then treated with different grades of calcium chlorite 0, 0.5, 1 and 1.5 percentage for five minutes, then were divided to two groups; packed and non packed with plastic cover. Then fruits were evaluated for changes in quantity parameters; pH, TA (Titratable acidity), TSS (Total soluble solids), Dry and fresh weight ratio, water content, Anthocyanin, Ascorbic acid, Ca2+, Sugar and pectin. The results showed that the packed fruits treated with calcium chloride (at 0.5 and 1 percentage) and chlorine (at 50 ppm) remained better when compared with non packed fruits. It was found that packing treatment had not a significant effect on pH. It can also deduce that packed treated fruits showed a lower TA, Anthocyanin, calcium, sugar and pectin while TSS, fresh to dry weight ratio, water content and ascorbic acid was higher in packed treated fruits.